Blood gas and serum biochemical RIs for healthy newborn Murrah buffaloes (Bubalus bubalis) - Santana, André M. [UNESP]; Silva, Daniela G. [UNESP]; Clemente, Virna [UNESP]; Pizauro, Lucas J. L. [UNESP]; Bernardes, Priscila A. [UNESP]; Santana, Clarissa H. [UNESP]; Eckersall, Peter D.; Fagliari, José J. [UNESP] (Wiley, 2018)
Background: There is a lack of published work on RIs for newborn buffaloes. Establishing blood gas and serum biochemical RIs for newborn buffaloes is important for monitoring health. Objectives: This study establishes blood gas and serum biochemical RIs of newborn buffaloes. Methods: Twenty-eight newborn buffaloes, 10–30 days old, were selected. Thirty blood biochemical variables were analyzed. The Anderson–Darling test was used to assess the normality of the distribution. The Dixon test and the Tukey test were used to identify outliers. The RI and 90% CI were determined using standard and robust methods and the Box–Cox transformation. Results: A total of 30 RIs for healthy buffalo calves have been reported in this study. RIs for blood gas variables were reported for pH, partial pressure of oxygen (pO2), partial pressure of carbon dioxide (pCO2), saturation of O2 (SO2), bicarbonate (cHCO3 −), base excess (BE), total carbon dioxide (ctCO2), and anion gap (AG). RIs for serum biochemical variables were reported for glucose (GLU), direct bilirubin (DB), total bilirubin (TB), AST, ALP, GGT, CK, LDH, creatinine (CREA), urea, cholesterol (CHOL), triglycerides (TG), Ca, P, Mg, Na, K, iCa, Cl, iron, total protein (TP), and albumin (ALB). Conclusions: This is the first reported study covering complete serum chemistry and blood gas RIs for healthy 1-month-old Murrah buffaloes.
Keywords: Bicarbonate; clinical biochemistry; diagnosis; neonatal; prognosis; water buffalo